Bezpieczeństwo terapii ranibizumabem w wysiękowej postaci AMD i rola naczyniowego czynnika wzrostu w procesie fizjologicznej angiogenezy - Figurska, Małgorzata; Robaszkiewicz, Jacek; Wierzbowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Vascular endothelial growth factor – A (VEGF-A), is a major factor implicated in choroidal neovascularisation (CNV) and therefore a target for therapeutic agents in wet age related macular degeneration (AMD). Ranibiuzumab (Lucentis) blocks all active isoforms of VEGF-A and the products of their degradation. It penetrates through all layers of the retina in order to reach the target tissue. It is quickly removed from the system and it is characterised by low level of immunogenicity. The essence of angiogenesis is formation of new vessels by branching and expansion of already existing ones. Angiogenesis is an important physiological process that takes place during the healing of wounds, reconstruction of hypoxic injury and reproduction. However some diseases such as cancer, arthritis, diabetes and neovascular AMD are associated with persistent unregulated angiogenesis. There is an important question whether binding vascular-endothelial growth factors in wet AMD therapies using ranibizumab is correlated with the increase of the incidence of systematic adverse effects (AEs), such as cardiovascular episodes or thrombosis. The aim of this article is to present ranibizumab as a safe drug in treating wet AMD patients. Even though the concentration of Lucentis administered in a dose of 0.3 or 0.5 mg into the vitreous body in the organism is very low, the incidence of AEs during the anti-VEGF therapy was traced. In MARINA and ANCHOR studies, occurrence of possible AEs was observed. No statistically significant differences were shown in the AEs frequency between the patients treated with ranibizumab and the control group, and in correlation with the general population of patients suffering from wet AMD.